Some aspects of complicated cataract surgery technique in patients with glaucoma - E. M. Kasimov; M. N. Pirmetov (Российский офтальмологический журнал)
According to literary data, 78.9 % of patients with cataract and glaucoma who receive cataract surgery have complications like sinechias, mioses, papillary membrane, or lens subluxation, which require additional surgical methods. Purpose: to evaluate the performance of a modified irrigation cannula applied in complicated cataract surgery in cases of a rigid pupil for the prevention of intra- and postoperative complications. Material and methods. The main group consisted of 30 patients (30 eyes) with narrow rigid pupils that were spread intraoperatively with an irrigation fork-shaped cannula, modified by the authors. The control group of 22 patients were operated using an iris retractor in the shape of hooks. Results. The evaluation took place during the surgery, in an early postsurgical period (up to 2 months) and in a late postsurgical period (1 year after the operation). During the surgery, 4 patients of the main group (13.3 %) and 11 patients of the control group (41 %) patients were found to have a hyphema. Patients without synechia had no hyphema. In an early postoperative period (1 week) 2 patients of the main group and 6 patients of the control group developed a 1-2 mm hyphema. In the late postoperative period all patients of the main group had round pupils with a diameter of 3-4 mm. In the control group, 3 patients showed a break in the pupillary edge of the iris, while 14 patients developed an irregular shape of the pupil which had total absence of reaction to light. Visual acuity of all patients of the main group was 0.7-0.8, while in the control group it was 0.4-0.6. Conclusion. When using the suggested fork shaped irrigation cannula in cataract surgery of patients with a narrow rigid pupil, there is no need for additional manipulations and multiple tools to check the capsular sack for lenticular masses, which reduces labor, risk of injury, and surgery duration. For citation: Kasimov E.M., Pirmetov M.N. Some aspects of complicated cataract surgery technique in patients with glaucoma. Russian ophthalmological journal. 2018; 11 (1): 12-5. doi: 10.21516/2072-0076-2018-11-1-12-15 (In Russian).